2021
DOI: 10.1002/ieam.4394
|View full text |Cite
|
Sign up to set email alerts
|

Linking field and laboratory studies: Reproductive effects of perfluorinated substances on avian populations

Abstract: Although both laboratory and field studies are needed to effectively assess effects and risk of contaminants to free‐living organisms, the limitations of each must be understood. The objectives of this paper are to examine information on field studies of reproductive effects of perfluorinated substances (PFASs) on bird populations, discuss the differences among field studies, and then place those results in context with laboratory studies. Hypotheses to explain the divergences between field studies and between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The large natural variation in hatching success, 2 orders of magnitude difference between NOAEL and LOAEL values that are both within the realm of environmental possibility, and exposure to PFAS as mixtures in the environment could collectively explain the variation witnessed among avian field studies (Custer et al 2012, 2014, 2019; Tartu et al 2014; Groffen et al 2019). These factors could also partially explain the discrepancy noted between field and laboratory studies (Custer 2021) with regard to the association observed between select PFAS concentrations in eggs and avian hatching success. This variation among avian study outcomes on hatching success highlights the importance of clear reporting in the absence of consistent or updated avian PFAS toxicology guidelines (Organisation for Economic Co‐operation and Development 1984; Office of Chemical Safety and Pollution Prevention 2012) and should encourage the examination of a broad range of reproductive health variables (i.e., not solely hatching success) when investigating chronic oral PFAS toxicity.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The large natural variation in hatching success, 2 orders of magnitude difference between NOAEL and LOAEL values that are both within the realm of environmental possibility, and exposure to PFAS as mixtures in the environment could collectively explain the variation witnessed among avian field studies (Custer et al 2012, 2014, 2019; Tartu et al 2014; Groffen et al 2019). These factors could also partially explain the discrepancy noted between field and laboratory studies (Custer 2021) with regard to the association observed between select PFAS concentrations in eggs and avian hatching success. This variation among avian study outcomes on hatching success highlights the importance of clear reporting in the absence of consistent or updated avian PFAS toxicology guidelines (Organisation for Economic Co‐operation and Development 1984; Office of Chemical Safety and Pollution Prevention 2012) and should encourage the examination of a broad range of reproductive health variables (i.e., not solely hatching success) when investigating chronic oral PFAS toxicity.…”
Section: Resultsmentioning
confidence: 96%
“…collectively explain the variation witnessed among avian field studies (Custer et al 2012(Custer et al , 2014(Custer et al , 2019Tartu et al 2014;Groffen et al 2019). These factors could also partially explain the discrepancy noted between field and laboratory studies (Custer 2021) 4). Dose-response modeling (Figure 3; log-logistic, 3 parameters, fixed upper limit at 18 d, drc package; R Development Core Team 2020) of the average northern bobwhite quail arrested embryonic development day relative to controls (18 d) predicted EC10 and EC20 values of 0.697 and 2.31 ng/mL, respectively, when chronically exposed in ovo via parental oral exposure to the 2.1 to 2.8:1 PFOS:PFHxA mixture (Table 5).…”
Section: Endpoints Statistical Analyses Thresholds and Dose Responsesmentioning
confidence: 95%
“…Although direct uptake of additives from ingested microplastics is clear for some additives of concern (e.g., PBDEs, metals), it has not been evaluated thoroughly for most chemicals associated with plastics (e.g., PAHs, phthalates and bisphenols/nonylphenols, PCBs, OCPs). PFAs are additional emerging contaminants of concern and should also be evaluated in association with microplastics [204,205]. This should be accomplished through controlled studies feeding microplastics with known initial chemical concentrations to birds and measuring uptake in various tissues, and will most likely involve laboratory studies, but field studies will also be beneficial for ecological relevance and for species not amenable to laboratory conditions (e.g., [156]).…”
Section: Recommendations For Future Studiesmentioning
confidence: 99%
“…These whole egg ∑PFAS residue values both represent chronic northern bobwhite quail reproductive toxicity, but at much different sum values, demonstrating that an ERA based on a PFOS TRV, measured or modeled ∑PFAS values, and assumed additive PFAS toxicity may underestimate health risk to avian receptors inhabiting PFAS-contaminated ecosystems (Conder et al, 2020;Divine et al, 2020;Gobas et al, 2020;Larson et al, 2018;Zodrow et al, 2021). The presence of PFAS interactions within an exposure solution and the lower exhibited toxicity of PFHxA relative to PFOS in northern bobwhite quail could also help to explain the discrepancies previously noted in correlation between PFAS egg concentrations and avian hatching success among and between avian PFAS field and laboratory toxicology studies (Custer, 2021;Dennis, Hossain, et al, 2021). These collective study results are important in that they both confirm and refute previous PFAS toxicology assumptions concerning the bioaccumulation and toxicity of PFAS based solely on chain length and functional group, and further exemplify the need for expanded PFAS toxicology testing to include simple PFAS mixtures (see Verreault et al, 2005;Holmström & Berger, 2008;McCarthy et al, 2017;Ankley et al, 2021;Zodrow et al, 2021).…”
Section: Whole Egg Residuementioning
confidence: 99%